A rare complication of Ramsey Hunt Syndrome: Sınus vein thrombosis - Ramiz Ahmedov; Fatma Polat; Neşe Çelebisoy (Türk Nöroloji Dergisi, 2011)
Ramsay-Hunt Syndrome (RHS) is a rare affection characterized by peripheral facial paralysis (PFP), skin eruption in the auricular canal and cochleovestibular symptoms. It is produced by varicella-zoster virus(VZV) reactivation at the geniculate ganglia. In elderly and immunocompromised individuals, the virus may reactivate to produce shingles (zoster). After zoster resolves, many elderly patients experience postherpetic neuralgia. Uncommonly, VZV can spread to large cerebral arteries to cause a spectrum of large-vessel vascular damage, ranging from vasculopathy to vasculitis, with stroke. In immunocompromised individuals, especially those with cancer or acquired immunodeficiency syndrome, deeper tissue penetration of the virus may occur (as compared with immunocompetent individuals), with resultant myelitis, small-vessel vasculopathy, ventriculitis, and meningoencephalitis. The polymerase chain reaction (PCR) analysis of cerebrospinal fluid remains the mainstay for diagnosing the neurologic complications of VZV during life. We report a case of Ramsay Hunt syndrome complicated with cerebral venous thrombosis. Patient received treatment with acyclovir and anticoagulation. Early treatment with acyclovir therapy and anticoagulation could improve the recovery rate of facial nerve palsy and sinus vein thrombosis.